2013
DOI: 10.1111/cpr.12038
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of ovarian cancer stem‐like cells is associated with epithelial to mesenchymal transition through an miRNA‐activated AKT pathway

Abstract: Our findings demonstrate that EMT contributed to enrichment of ovarian CSCs in vitro, making EMT targeting in epithelial ovarian cancer a novel therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 42 publications
2
61
0
Order By: Relevance
“…Here, we reported that overexpression of miR-200c results in low levels of p-PI3K and p-AKT and that this phenomenon could be rescued by Sox2. Luo and colleagues have reported that the miR-20a/miR-200c-PTEN-AKT axis regulates EMT-associated CSC enrichment of epithelial ovarian cancer (EOC) cells (47). In this axis, miR200c expression was significantly higher in EOC spheroid cells, which produce large numbers of CSC cells, and activated the PI3K-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we reported that overexpression of miR-200c results in low levels of p-PI3K and p-AKT and that this phenomenon could be rescued by Sox2. Luo and colleagues have reported that the miR-20a/miR-200c-PTEN-AKT axis regulates EMT-associated CSC enrichment of epithelial ovarian cancer (EOC) cells (47). In this axis, miR200c expression was significantly higher in EOC spheroid cells, which produce large numbers of CSC cells, and activated the PI3K-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian CSLCs were enriched as previously described (21). Upon reaching 80% confluence, the SKOV3 cells were dissociated by 0.25% Trypsin-EDTA (Life Technologies, Carlsbad, CA, USA) for 1-2 min at 37˚C.…”
Section: Enrichment Of Cslcsmentioning
confidence: 99%
“…The migratory ability of the cells was determined by Transwell assay as previously described (21). Briefly, the cells were seeded into the top chamber of 8.0 µm Transwell invasion chambers (Corning Inc., Corning, NY, USA) in serum-free medium.…”
Section: Enrichment Of Cslcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has suggested that miRNAs play crucial roles in many biological processes, such as development, cell proliferation, invasion, migration and differentiation 20, 21, 22, 23, 24. Mutations of miRNA‐encoding genes or aberrant expression of miRNAs have been well described in various tumours, including gastric, breast and lung cancers, as well as glioblastoma and melanoma 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%